KINERJA DINAS KESEHATAN DALAM MENEKAN ANGKA HIV (HUMAN IMMUNODEFICIENCY VIRUS) / AIDS (ACQUIRED IMMUNODEFICIENCY SYNDROME) DI KABUPATEN BADUNG - Triana Widayani, Dewa Ayu; Supriliyani, Ni Wayan; Purnamaningsih, Putu Eka (CITIZEN CHARTER; Vol 4 No 1 (2024): Vol.4 No.1, 2024)
The Health Office is the implementing unit for health services in Badung Regency, which has a role in dealing with health problems that occur in Badung Regency. One of the phenomena of health problems in Badung Regency is the spread of Human Immunodeficiency Virus (HIV) and Acquired Immune Syndrome (AIDS). This research was conducted at the Badung District Health Office and is comprehensive and continuous in Badung District. The purpose of this study was to describe the performance of the Badung District Health Office in preventing and controlling HIV/AIDS in the people of Badung District. Performance indicators based on Agus Dwiyanto's theory are: Productivity, Service Quality, Responsiveness, Responsibility, Accountability. The method used is qualitative with a descriptive approach. Data collection is done by interviews, observation, documentation. Data analysis techniques through data reduction, data presentation, drawing conclusions. The results showed that the performance of the Badung District Health Office in reducing HIV/AIDS rates was running well but not fully optimal. This is because there are still several obstacles, namely the lack of human resources at health service centers in Badung Regency in carrying out the HIV/AIDS prevention and control program, the lack of stock of drugs and condoms that should be given to the community, the lack of knowledge from the community regarding understanding of prevention and control. HIV/AIDS because the interest of the people who participate in socialization is small. Recommendations that can be given are recruiting new officers for handling HIV/AIDS in all health service centers in Badung Regency, increasing the availability of existing facilities and infrastructure at health service centers in Badung Regency, and also increasing public knowledge regarding HIV/AIDS. AIDS, namely by utilizing technology by spreading information on social media. Keywords: Badung District Health Office, HIV/AIDS, Performance